Addition of Bioactive Glass Decreases Setting Time and Improves Antibacterial Properties of Mineral Trioxide Aggregate - Amin Salem Milani; Faezeh Hadinia; Yashar Rezaei; Mohammad Hossein Soroush Barhaghi; Kamal Attari; Ahmad Nouroloyouni (International Journal of Biomaterials)
Objectives. This study aimed to assess the effect of addition of bioactive glass (BG) on the setting time and antibacterial activity of mineral trioxide aggregate (MTA) against Enterococcus faecalis (E. faecalis). Materials and Methods. In this in vitro study, BG was synthesized by the sol-gel technique and added to MTA powder in certain ratios. Three groups of specimens were fabricated from pure MTA, MTA mixed with 10wt% BG, and MTA mixed with 20wt% BG. The setting time of specimens was measured according to ISO9917-2007. Direct contact test was used to assess the antimicrobial activity of the three groups against E. faecalis. Data were analyzed by repeated measures ANOVA (alpha = 0.05). Results. Addition of BG (in both concentrations) to MTA decreased its setting time and improved its antibacterial activity against E. faecalis (p<0.05). By an increase in concentration of BG (20%), the antimicrobial activity further improved (p<0.05). Conclusion. Addition of BG to MTA in 10wt% and 20wt% concentrations decreased its setting time and improved its antibacterial activity against E. faecalis.